Iron Uptake Analysis in a Set of Clinical Isolates of Pseudomonas putida - Molina, Lázaro; Geoffroy, Valérie A.; Segura, Ana; Udaondo, Zulema; Ramos, Juan-Luis (Frontiers in Microbiology, 2016)
Pseudomonas putida strains are frequent inhabitants of soil and aquatic niches and they are occasionally isolated from hospital environments. As the available iron sources in human tissues, edaphic and aquatic niches are different, we have analyzed iron-uptake related genes in different Pseudomonas putida strains that were isolated from all these environments. We found that these isolates can be grouped into different clades according to the genetics of siderophore biosynthesis and recycling. The pyoverdine locus of the six Pseudomonas putida clinical isolates that have so far been completely sequenced, are not closely related; three strains (P. putida HB13667, HB3267 and NBRC14164T) are grouped in Clade I and the other three in Clade II, suggesting possible different origins and evolution. In one clinical strain, P. putida HB4184, the production of siderophores is induced under high osmolarity conditions. The pyoverdine locus in this strain is closely related to that of strain P. putida HB001 which was isolated from sandy shore soil of the Yellow Sea in Korean marine sand, suggesting their possible origin and evolution. The acquisition of two unique TonB-dependent transporters for xenosiderophore acquisition, similar to those existing in the opportunistic pathogen P. aeruginosa PAO, is an interesting adaptation trait of the clinical strain P. putida H8234 that may confer adaptive advantages under low iron availability conditions.